Short course of steroids in home treatment of children with acute asthma. - Deshpande, A (1986)
A double blind, randomised, placebo controlled study of the treatment of children with acute asthma at home showed that a three day course of prednisolone hastened improvement of both asthmatic symptoms and peak expiratory flow rates. Thus all asthmatic children who present with an acute attack should be considered for treatment with corticosteroids in addition to bronchodilators not only to prevent possible deterioration but also to speed recovery.